Pneumococcal RNase R globally impacts protein synthesis by regulating the amount of actively translating ribosomes - Bárria, Cátia (RNA Biol, 2019)
Ribosomes are macromolecular machines that carry out protein synthesis. After each round of translation, ribosome recycling is essential for reinitiating protein synthesis. Ribosome recycling factor (RRF), together with elongation factor G (EF-G), catalyse the transient split of the 70S ribosome into subunits. This splitting is then stabilized by initiation factor 3 (IF3), which functions as an anti-association factor. The correct amount of these factors ensures the precise level of 70S ribosomes in the cell. RNase R is a highly conserved exoribonuclease involved in the 3ʹ to 5ʹ degradation of RNAs. In this work we show that pneumococcal RNase R directly controls the expression levels of frr, fusA and infC mRNAs, the corresponding transcripts of RRF, EF-G and IF3, respectively. We present evidences showing that accumulation of these factors leads to a decreased amount of 70S active particles, as demonstrated by the altered sucrose gradient ribosomal pattern in the RNase R mutant strain. Furthermore, the single deletion of RNase R is shown to have a global impact on protein synthesis and cell viability, leading to a ~50% reduction in bacterial CFU/ml. We believe that the fine-tuned regulation of these transcripts by RNase R is essential for maintaining the precise amount of active ribosomal complexes required for proper mRNA translation and thus we propose RNase R as a new auxiliary factor in ribosome reassociation. Considering the overall impact of RNase R on protein synthesis, one of the main targets of antibiotics, this enzyme may be a promising target for antimicrobial treatment.